Cationic Ring Opening polymerization of ε-caprolactam by a Montmorillonite Clay Catalyst - Djamal Eddine Kherroub; Mohammed Belbachir; Saad Lamouri (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
The ring opening bulk polymerization of ε-caprolactam catalyzed by Maghnite-H+ was reported. Maghnite-H+ is a montmorillonite silicate sheet clay was prepared through a straight forward proton exchange process. The effect of the amount of catalyst, and temperature was studied. Increasing Maghnite-H+ proportion and temperature produced the increase in ε-caprolactam conversion. The kinetics indicated that the polymerization rate is first order with respect to monomer concentration. Mechanism studies showed that monomer inserted into the growing chains with the acyl–oxygen bond scission rather than the break of alkyl–oxygen bond. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)